Stylistics and language teaching : with a section on translation studies - Suresh Kumar, 1937- (Delhi : Kalinga Publications, 2003)
With reference to Hindi language in India.
Includes bibliographical references (p. 227-240).
Mode of access: Internet.
Includes some passages in Hindi.
Keywords: Hindi language -- Rhetoric -- Study and teaching; Hindi language -- Semantics; Discourse analysis; Hindi language -- Style